Investigating social inequalities in older adults’ dentition and the role of dental service use in 14 European countries - Shen, Jing; Listl, Stefan (The European journal of health economics, 2018)
BackgroundOral disease, despite being largely preventable, remains the most common chronic disease worldwide and has a significant negative impact on quality of life, particularly among older adults.ObjectiveThis study is the first to comprehensively and at a large scale (14 European countries) measure the social inequalities in the number of natural teeth (an informative oral health marker) in the over 50-year-old population and to investigate the extent to which such inequalities are attributable to dental service use.MethodsUsing Wave 5 of the Survey of Health, Ageing and Retirement in Europe, which included internationally harmonized information on over 50,000 individuals across 14 European countries, we calculated Gini and Concentration indices (CI) as well as the decompositions of CIs by socioeconomic factors.ResultsSweden consistently performed the best with the lowest inequalities as measured by Gini (0.1078), CI by income (0.0392), CI by education (0.0407), and CI by wealth (0.0296). No country performed the worst in all inequality measures. However, unexpectedly, some wealthier countries (e.g., the Netherlands and Denmark) had higher degrees of inequalities than less-wealthy countries (e.g., Estonia and Slovenia). Decomposition analysis showed that income, education, and wealth contributed substantially to the inequalities, and dental service use was an important contributor even after controlling for income and wealth.ConclusionsThe study highlighted the importance of comprehensively investigating oral health inequalities. The results are informative to policymakers to derive country-specific health policy recommendations to reduce oral health inequalities in the older population and also have implications for oral health improvement of the future generations.